Chemical composition, character and reactivity of renewable fuel ashes. (15th July 2016) - Magdziarz, Aneta; Dalai, Ajay K.; Koziński, Janusz A.
Highlights: Renewable fuel ashes from different origin were analyzed. Characterization and comparison of studied ashes were given. Transformation of inorganic components was determined using XRD and FTIR. The ash fusion behaviour of ashes was studied experimentally. Empirical indices were calculated indicating slagging and fouling propensities. Abstract: The paper is focused on the characterization of renewable fuel ashes and their impact on fouling and slagging during combustion. Biomass (A1) and sewage sludge (A2, A3) ashes were investigated for characterization of their corrosive properties. The chemical and phasemineral composition of ashes were studied using a variety of analytical techniques including XRF, ICP-MS, XRD, SEM–EDS, and the ash fusion characteristics by using a thermal microscope. The slagging and fouling indices, as well as thermal conductivity, were calculated and the sintering properties were predicted. The studied ashes had different concentrations of the main chemical compounds and mineral phases. The XRF results showed that CaO, SiO2, K2 O, MgO, P2 O5 and Al2 O3 are the main compounds of A1 and A3 ashes, whereas Na2 O and SO3 dominated in A2. Consequently, SEM images showed surface differences between ash particles. Phase analyses indicated the existence of corrosive phases containing potassium and sodium K2 Ca(CO3 )2, KAlSi2 O6, KCl, NaAlSiO4 (A1) and Na2 SO4, NaCl (A2). Such compounds can decrease the sintering temperature due to formation of low temperature eutectics. The lowest fusion temperatures below 1000 °C were detected from the sewage sludge ash A2 and above 1200 °C from A1 and A2 with high Ca, Si and Al contents.